Analysis of profitability of financial results and factors of its change - Agabekova, G.N.; Agabekova, Sh.N.; Maulenkulova, G.Ye.; Arapbaeva, Zh.Sh.; Orazbayeva, A.B. (Karagandy University of the name of acad. E.A. Buketov, 2023)
Object: It lies in the fact that profit and profitability play an important role in the process of the company's activities. They show how stable the company is in carrying out its activities and effective in achieving its goals.The object of the study is to develop recommendations for their improvement based on the analysis of the profit and profitability of the activities of “Kazakhstan Waste Management Operator” LLP. Methods: In the process of writing a scientific article, the following methods of scientific cognition were used: observation, grouping, generalization, comparison, questionnaire, analysis, synthesis. When writing the work, such research methods as the method of analysis and synthesis, comparative, system, factor methods, as well as accounting methodologies, financial and tax reporting were used. Findings: Profit and profitability indicators are formed under the influence of a large number of interrelated factors that affect the results of the organization's work in different directions: some are good, others are negative. Moreover, the negative impact of some factors can reduce or even negate the positive impact of others. Thorough consideration of the factors affecting the key indicators of the enterprise can help to achieve an understanding of the formation of profits at the enterprise, as well as reduce unnecessary costs. The variety of factors affecting profit and profitability requires their classification, which at the same time is important for determining the main directions of searching for reserves to improve the efficiency of management. Conclusions: In the course of the analysis, reserves for improving profit and profitability indicators were identified, and recommendations were also proposed. The main directions among which are an increase in the volume of provided services, and, accordingly, an increase in revenue, and a reduction in the costs of the enterprise.
Қаржылық нәтижелердің табыстылығын және оның өзгеру факторларын талдау
Анализ рентабельности финансовых результатов и факторов ее изменения
Keywords: analysis of financial results; accounting statements; profitability coefficients; taxable profit (tax loss); nominal profit; operating profit; profit; profit from financial activities; real profit; invoice